170821 初版 170821 更新
\(\sin 2\theta=2\sin\theta\cos\theta\)
\(\cos 2\theta=\cos^2\theta-\sin^2\theta=2\cos^2\theta-1=1-2\sin^2\theta\)
\(\tan 2\theta=\dfrac{2\tan\theta}{1-\tan^2\theta}\)
加法定理 より ただち。
\(\sin 2\theta=\sin(\theta+\theta)\)
\(=\sin\theta\cos\theta+\cos\theta\sin\theta=2\sin\theta\cos\theta\)
\(\cos 2\theta=\cos(\theta+\theta)\)
\(=\cos\theta\cos\theta-\sin\theta\sin\theta=\cos^2\theta-\sin^2\theta\)
また,\(\cos^2\theta-\sin^2\theta=\cos^2\theta-(1-\cos^2\theta)
=2\cos^2\theta-1\)
さらに,\(\cos^2\theta-\sin^2\theta=(1-\sin^2\theta)-\sin^2\theta
=1-2\sin^2\theta\)
\(\tan 2\theta=\dfrac{\tan\theta+\tan\theta}{1-\tan\theta\tan\theta}
=\dfrac{2\tan\theta}{1-\tan^2\theta}\)